Síndrome de conn causada por adenoma de adrenal-tratamento por videolaparoscopia - Puttini, Sinthia Maria Benigno (2003)
The authors present a case-report a 43 years old, female patient presenting with an eight-year history of hypertension caused by an adrenal adenoma. Hypokalemia and supressed plasma renina confirmed the diagnosis of primary hyperaldosteronism. An abdominal computed tomography revealed a right adrenal mass. The patient was successfully treated laparoscopically. The histopathological diagnosis was adenoma. The patient had normal blood pressure within three months.